2021
DOI: 10.1186/s13148-021-01204-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylation patterns in Marfan syndrome

Abstract: Background Marfan syndrome (MFS) is a connective tissue disorder caused by mutations in the Fibrillin-1 gene (FBN1). Here, we undertook the first epigenome-wide association study (EWAS) in patients with MFS aiming at identifying DNA methylation loci associated with MFS phenotypes that may shed light on the disease process. Methods The Illumina 450 k DNA-methylation array was used on stored peripheral whole-blood samples of 190 patients with MFS ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Thus, patients with variants of high risks of aortic events should receive more frequent examinations while those carrying less deleterious variants should not be exempted from follow-up, considering the life-long risks of aortic dissection ( Gaudry et al, 2021 ). Researchers have explored other factors contributing to the phenotypes, including FBN1 expression at mRNA and protein level ( Aoyama et al, 1994 ; Aubart et al, 2015 ), modifying genes ( Aubart et al, 2018 ), and epigenetic factors ( van Andel et al, 2021 ). Thus, a prediction model of phenotype and prognosis is warranted in the future which should incorporate both genotypes and modifying factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, patients with variants of high risks of aortic events should receive more frequent examinations while those carrying less deleterious variants should not be exempted from follow-up, considering the life-long risks of aortic dissection ( Gaudry et al, 2021 ). Researchers have explored other factors contributing to the phenotypes, including FBN1 expression at mRNA and protein level ( Aoyama et al, 1994 ; Aubart et al, 2015 ), modifying genes ( Aubart et al, 2018 ), and epigenetic factors ( van Andel et al, 2021 ). Thus, a prediction model of phenotype and prognosis is warranted in the future which should incorporate both genotypes and modifying factors.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic factors were found to influence the aortic manifestations and progression in patients with MFS too. Van Andel et al identified 28 differentially methylated regions (DMPs) associated with aortic diameters, 7 DMPs with aortic diameter growth, and 5 DMPs with aortic events by genome-wide DNA-methylation profiling of peripheral whole-blood samples ( van Andel et al, 2021 ). Meanwhile, around 0.64% of MFS patients carried more than one FBN1 gene variant which could be overlooked in routine examinations ( Arnaud et al, 2017 ).…”
Section: Other Factors Contributing To Phenotypementioning
confidence: 99%
“…[5][6][7] MFS exhibits considerable phenotypic variation, including within families that carry the same genetic mutation. 8 Numerous patient characteristics have been explored to explicate the significant phenotypic variation observed in MFS. 9 A diverse array of mutation types and sites in the FBN1 gene has been linked to disease severity and response to pharmaceutical interventions.…”
Section: Introductionmentioning
confidence: 99%
“…MFS exhibits considerable phenotypic variation, including within families that carry the same genetic mutation 8 . Numerous patient characteristics have been explored to explicate the significant phenotypic variation observed in MFS 9 .…”
Section: Introductionmentioning
confidence: 99%
“…MFS exhibits considerable phenotypic variation, including within families that carry the same genetic mutation [7]. Numerous patient characteristics have been explored to explicate the signi cant phenotypic variation observed in MFS [8].…”
Section: Introductionmentioning
confidence: 99%